2021
DOI: 10.1155/2021/6633442
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Comprehensive Analysis of Inflammation-Related ceRNA Networks and Tissue-Infiltrating Immune Cells in Ulcerative Colitis Progression

Abstract: Ulcerative colitis (UC) is a common disease with great variability in severity, with a high recurrence rate and heavy disease burden. In recent years, the different biological functions of competing endogenous RNA (ceRNA) networks of long noncoding RNAs (lncRNAs) and microRNAs (miRs) have aroused wide concerns, the ceRNA network of ulcerative colitis (UC) may have potential research value, and these expressed noncoding RNAs may be involved in the molecular basis of inflammation recurrence and progression. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…ENTPD1-AS1, located on chromosome 10q24.1, and also known as RP11-429G19.2, was involved in the immune-related pathways of in ammation recurrence in ulcerative colitis [35], and was demonstrated to be a predictor of prognosis of glioblastoma multiforme [36]. Our study results revealed that the three pyroptosis-related lncRNAs used to assess the risk model were independent prognostic factors of clinical stage and could robustly predict the prognosis of AEG.…”
Section: Discussionmentioning
confidence: 74%
“…ENTPD1-AS1, located on chromosome 10q24.1, and also known as RP11-429G19.2, was involved in the immune-related pathways of in ammation recurrence in ulcerative colitis [35], and was demonstrated to be a predictor of prognosis of glioblastoma multiforme [36]. Our study results revealed that the three pyroptosis-related lncRNAs used to assess the risk model were independent prognostic factors of clinical stage and could robustly predict the prognosis of AEG.…”
Section: Discussionmentioning
confidence: 74%
“…SH3BP5-AS1 is closely related to PC drug resistance. Only two studies have reported that SH3BP5-AS1 might be related to in ammation and the prognosis of head and neck tumors [9,23] ; however, the role of SH3BP5-AS1 has not been studied in PC. It is important to fully elucidate the mechanism of SH3BP5-AS1 in the drug resistance of PC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent efforts, the treatment and diagnosis of IBD remains a challenge in clinical studies ( 27 , 28 ). Thus, recent studies have aimed to investigate the underlying molecular mechanisms of IBD development and disease progression ( 29-31 ). lncRNAs are critical diagnostic and therapeutic biomarkers, which act as competitive endogenous RNAs ( 32 ).…”
Section: Discussionmentioning
confidence: 99%